PENGARUH PENYULUHAN PENGGUNAAN ANTIBIOTIKA TERHADAP TINGKAT PENGETAHUAN MASYARAKAT DI KOTA MANADO - Wowiling, Chalvy; Goenawi, Lily Ranti; Citraningtyas, Gayatri (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTThe high number of inappropriate of antibiotics in community due to lack of knowledgeabout the use of antibiotics may lead the increasing of antibiotic resistance. This study aimedto measure the people’s knowledge before and after following health education and analyzethe effect of health education of antibiotic administration to community knowledge. This is apre-experimental study in community with one group pretest-posttest design using aquestionnaire. Result of this study show the number of respondent with lack of knowledgebefore the education is 53,3% decrease after education which is 17,3%, number of respondentwith quite good increase from 37,3% become 42,7%, and respondent with good knowledgeincrease from 9,3% become 40%. Mean of knowledge score after following health education70,53 is higher than before following health education 55,53, so H1 is accepted withsignificant value 0.000 (p<0,05). Health education can increase public knowledge aboutantibiotic administration.Keywords : antibiotic, health education , people of Manado City